2020
DOI: 10.1002/lary.29265
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Tobacco Use Among Students: The U.S. Smokeless Tobacco Company College Marketing Program

Abstract: Objectives/Hypothesis: From the 1970s-1990s the U.S. Smokeless Tobacco Company (USST) conducted aggressive campaigns to solicit college students to buy their smokeless tobacco (ST) products. The scope, scale, methods, and impact of this youth marketing campaign have yet to be analyzed in the academic literature.Study Design: Historical research study. Methods: Internal industry documents describing the USST campaigns were obtained via the University of California, San Francisco's repository of tobacco company … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition to COVID, which has multiple otolaryngological manifestations, other areas within our specialty have been affected. For example, smokeless tobacco was promoted as a safer alternative to cigarettes, despite the risk of oral cancer with either method 7 . Subsequent data demonstrated that 18% of health‐related claims related to tobacco were false 8 .…”
Section: Falsehood Spreads Fastermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to COVID, which has multiple otolaryngological manifestations, other areas within our specialty have been affected. For example, smokeless tobacco was promoted as a safer alternative to cigarettes, despite the risk of oral cancer with either method 7 . Subsequent data demonstrated that 18% of health‐related claims related to tobacco were false 8 .…”
Section: Falsehood Spreads Fastermentioning
confidence: 99%
“…For example, smokeless tobacco was promoted as a safer alternative to cigarettes, despite the risk of oral cancer with either method. 7 Subsequent data demonstrated that 18% of health-related claims related to tobacco were false. 8 In addition, Formeister et al, 9 studied sensorineural hearing loss to provide a scientific assessment of a previously publicized risk.…”
Section: Falsehood Spreads Fastermentioning
confidence: 99%
“…The tobacco industry has an established history of targeting products to specific consumer segments in the U.S., including youth and young adults, women, and systematically marginalized groups based on race, ethnicity, or sexual identity ( Ling and Glantz, 2002 , Stevens et al, 2004 , Toll and Ling, 2005 , Cruz et al, 2019 , Barbeau et al, 2005 ). Exposure to tobacco marketing is associated with increased tobacco consumption, including increased likelihood of initiation ( Cruz et al, 2019 , DiFranza et al, 2006 , Kreitzberg et al, 2019 , Qian et al, 2021 , Nicksic et al, 2017 ). Studies suggest that exposure to tobacco ads among youth is substantial ( Agaku et al, 2014 , Marynak et al, 2018 ), and there is growing evidence of comparatively higher exposure to commercial tobacco ads among individuals who identify as racial, ethnic, and sexual minorities (e.g., bisexual Latinas) versus those who identify as heterosexual and White ( Tan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%